Gambaran Motivasi Berwirausaha pada Pengusaha Kosmetik yang Pantang Menyerah - Febriani, Fipi; Rahmi, Tuti (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to examine the entrepreneurial motivation of resilient cosmetics entrepreneurs. This study employs a qualitative method with a phenomenological approach. The research participants consist of two individuals: a male and a female cosmetics entrepreneur. Data collection was conducted through semi-structured interviews. Data analysis was carried out using Interpretative Phenomenological Analysis (IPA), which emphasises the process of reflecting on and interpreting the participants’ life experiences. The stages of analysis included repeated reading of the transcripts, initial note-taking, the development of emergent themes, the grouping of themes, and an in-depth interpretation of the meaning of the participants’ experiences. Data validity was ensured through credibility techniques, namely source triangulation and the verification of interpretative results with the participants. The research findings indicate that entrepreneurial motivation is influenced by intrinsic factors such as a desire for independence, interest, and a desire to improve well-being, as well as extrinsic factors such as social support, work experience, and market opportunities. Furthermore, aspects of risk tolerance, business viability, and a desire to work independently are key factors in driving the success of a cosmetics business.